Um município de pequeno porte sob o olhar da produção do espaço urbano: as várias formas de segregação em São João Nepomuceno MG - Maurício Henriques Velasco (2020)
This work has as main purpose to reveal the several process of segregation in the city of São João Nepomuceno, by using as its basis the constitution and the constant changes at the urban space, and by connecting the several dynamics at the territorial structure with those ones of social structure. This process will be studied since the evolution of its urban footprint over time, and also from the profile of state acting in symbiosis with other actors at the development of this space, specially the industrial capitals of textile and clothing production sectors. One of the great contributions in this effort is to perceive the segregation in territorial structure shaping of a small urban organism, by setting several relationships with segregation phenomena already studied for Brazilian cities.